A concepção e criação do caractere tridimensional: metodologia da criação e desenvolvimento de personagens tridimensionais para games - Musarra, Fábio Luiz Livramento Barretto (2011)
This research investigates the artistic-ontological fundaments of the Human Figure conception, choosing its history and describing the thematically evolution which tangents the human being image conception. Analyzing the evolution process in the paintings and Greek sculpture, discusses its influences in works from the Masters of the Renaissance, who are considered as the source of current concepts in the tridimensional modeling area of the human figure. From this context, the ontological properties are organized and they regulate the modeling of the human figure inside the digital environment of the tridimensional modeling software, based in a derivative pragmatic of a tophilosophical position. Inside this perspective introduces and defines the concept of the character, establishing it to the methodological process of the tridimensional modeling of the human figure. As the object of this research, it is dedicated the sequential and normative exposition of a character modeling, structuring its steps and its ontological organization from its conceptual properties, showing its connection and fundament in the tradition of the Renaissance Masters. It is accomplished the application of the concept of tridimensional modeling of characters in the presentation of digital artists innovation in the current representation of the human figure, which suits as a base to the tridimensional to the composition of games and metaverses characters. It concludes with the exposition and proposal of a pragmatic that can guide the character modeling to the Digital Design of Interactive Environments